Knowledge brokers within the multiple streams framework: The science-policy interface for livestock and climate change discussions in Kenya - Cramer, Laura K.; Crane, Todd A.; Dewulf, Art (Elsevier, 2023)
Livestock production is affected by climate change but also contributes to climate change through greenhouse gas emissions. This leads to ambiguity in how livestock are framed in climate and development policy processes. We use the Multiple Streams Framework (MSF) to investigate the role of knowledge brokers in Kenyan livestock and climate change policy processes. We analyze how knowledge brokers deal with ambiguity from different problem and response framings within science-policy interfaces using the case of a project that seeks to inform Kenyan policies relevant to livestock and climate change. We identify ambiguity within the problem stream where actors recognize adaptation and mitigation as dual challenges of livestock and climate change. This ambiguity creates tension between actors but can be strategically deployed to help match the problem and policy streams. Actors use the terms ‘climate smart’ and ‘co-benefits’ to link the dual adaptation and mitigation needs. In the political stream, nationally defined priorities and external funding possibilities influence the political will and motivation to adopt identified response options. There are opportunities for knowledge brokers to address the ambiguities and translate knowledge during windows of opportunity when the streams are being coupled. Still, challenges exist, resulting in the slow and inadequate development of policies. This paper makes two contributions to the MSF literature. First, we further refine the concept of knowledge brokers and establish their role across all three streams. Second, we apply the MSF in a lower-income country and demonstrate that international organizations must be among the actors considered.